Cryptogenic Organizing Pneumonia with a Rare Radiographic Presentation of a Diffuse Micronodular Pattern Mimicking Miliary Lung Infiltration: A Case Report and Review of the Literature. (3rd January 2020) - Kewcharoen, Jakrin; Poonsombudlert, Kittika; Sathirareuangchai, Sakda; Sae-Ow, Wichit; La, Hanh; Sriratanaviriyakul, Narin
Abstract : We reported a case of cryptogenic organizing pneumonia (COP) presenting with an unusual diffuse micronodular pattern (DMP) mimicking miliary lung infiltration. The patient is a 66-year-old man with a past medical history of diabetes mellitus type 2 and hyperlipidemia who presented with progressive dyspnea associated with significant weight loss and night sweats for 2 weeks. Upon admission, the patient's clinical condition rapidly progressed to respiratory failure requiring mechanical ventilation. Initial Chest X-ray (CXR) showed diffuse reticulonodular infiltration mimicking miliary pattern. Chest computed tomography (CT) showed diffuse centrilobular micronodular infiltrations with features of a tree-in-bud pattern consistent with the CXR findings. He was then started on empiric antibiotics for community-acquired pneumonia and underwent a diagnostic bronchoscopy with alveolar lavage and transbronchial biopsies, which yielded negative cultures and unrevealing pathology. Tissue from CT-guided lung biopsy performed later on was also inconclusive. Due to the lack of clinical improvement, he eventually underwent surgical lung biopsy. The pathology result showed organizing pneumonia (OP) pattern with heavy lymphoplasmacytic infiltrates and numerous multinucleated giant cells. His final culture results, microbiological data and serology workup for autoimmune disease were all unremarkable. The patient was diagnosed with COP and was started on systemic corticosteroids. He displayed dramatic clinical improvement and was successfully liberated from the ventilator. Subsequent chest imaging showed resolution of the reticulonodular infiltrations. Early diagnosis for OP and ability to distinguish OP from infectious pneumonitides are critical as the majority of patients with OP respond promptly to corticosteroids. Common findings of radiographic pattern for OP are patchy air space consolidation or ground-glass opacity, yet DMP is another rare radiographic pattern that must be recognized, especially in COP. In summary, this case illustrates a rare radiographic presentation of COP. With early recognition and prompt diagnosis, proper treatment can significantly prevent morbidity and reduce mortality.